The impact of foreign direct investment, labour force, and external debt on economic growth in Indonesia and Malaysia - Cahyadin, Malik; Tamat Sarmidi (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study aims to estimate the impact of Foreign Direct Investment (FDI), labour, and external debt on economic growth in Indonesia and Malaysia over the period 1980-2016. The findings are expected to serve as a reference for macroeconomic policies in Indonesia and Malaysia. Employing an Autoregressive Distributed Lag Model (ARDL) and Error Correction Model (ECM), we find that FDI, labour force and external debt have a significant impact on the economic growth in the long- and short- run in both countries. Statistically, the estimated models are stable. Therefore, it is recommended that the authorities in Indonesia and Malaysia should concentrate on attracting more quality FDI inflows and properly manage external debts as well as high-skilled labour force, which are vital to economic growth.